Isolation of Flavonoid Compounds from Eceng Gondok (Eichhornia crassipes) and Antioxidant Tests with DPPH (1,1-Diphenyl-2-Picrylhydrazyl) Method - Kautsar Elvira; Enny Fachriyah; Dewi Kusrini (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
The research had been conducted of the isolation of flavonoid compounds from water hyacinth plants (Eichhornia crassipes) and antioxidant activity test by DPPH (1,1-diphenyl-2-picrylhydrazyl) method. This research starts from maceration of water hyacinth with ethanol solvent. Ethanol extract was hydrolyzed with HCl. Flavonoid separation is carried out by column chromatography and preparative thin layer chromatography. The obtained isolates were analyzed by UV vis spectrophotometer and FTIR spectrophotometer. Antioxidant activity was carried out by DPPH method. Flavonoid isolates were obtained as heavy as 4.5 mg (0.006%). The results of the analysis of flavonoid isolates A4a with UV vis spectrophotometer appear at a wavelength of 368 nm (band I) and 260 nm (band II). The results of the analysis with FTIR shown that the isolates had functional groups O-H, aliphatic C-H, CH3, C =O, aromatic C = C, and C-O ether, it was suspected that flavonoid isolates had a basic structure of quercetin 7-methyl ether compounds. The results of antioxidant activity test of flavonoid isolates shown IC50 price of 254.66 mg / L